Komunitas Bakteri pada Saluran Pencernaan Lobster Mutiara (Panulirus ornatus) - Arba’i Kartini Nurhasanah; Faturrahman Faturrahman (LPPM Universitas Mataram, 2019)
The presence of microbial communities in the digestive tract affects the physiological functions of digestion. The purpose of this study is to determine the bacterial community in the digestive tract of lobsters, especially pearl lobsters. This research is descriptive explorative. Samples were taken from the lobster digestive tract which was divided into 3, namely the cardiac, pylorus and intestinal sections and each part was counted for the total bacteria using the TPC (Total Plate Count) method. Then isolated from the Sea Water Complex media and partially characterized. The results showed that the total number of bacterial cells in cardiac, piloric and intestinal cells were 41.91 x 108 cfu.ml-1, 18.26 x 108 cfu.ml-1 and 14.10 x 108 cfu.ml-1 respectively. The number of bacterial isolates obtained from the lobster pearl digestive tract were 51 isolates with details of 18 cardiac isolates, 16 isolates in piloric, and 17 isolates in the intestine. Phenotypic isolates obtained from lobster digestive tract bacteria consisted of monococcus 37.25%, diplococcus 27.45%, streptococcus 29.41%, staphylococcus 1.96%, and long baccil 3.92%, while gram positive 62.65 % and gram negative at 37.25%